Examining the Dynamics of Labour Force Participation, Carbon Dioxide Emission and Population Health in Sub-Saharan Africa - Oyedele, Ovikuomagbe; Tella, Sheriffdeen Adewale (International Journal of Energy Economics and Policy, 2023)
This study examined the dynamic causal relationship between population health, carbon dioxide (CO2) emission and labour force participation. The study employed the block exogeneity wald test after estimating a panel VAR model using data for 24 sub-Saharan African countries from 1990 to 2018. The dynamic interactions among the variables and effect of shocks was also examined using the variance decomposition analysis and impulse response functions. For robustness, the estimation was done using both aggregate labour force participation and disaggregated labour force participation inorder to investigate the differentials by gender. The results showed evidence of a feedback effect between life expectancy and total labour force participation. This also holds for male labour force participation however, a unidirectional causality was found from female labour force participation to life expectancy. A one standard deviation shock in CO2 emission had a negative impact on life expectancy. Life expectancy also had the greatest contribution to variations in CO2 emission. Male labour force participation shocks had a consistently negative impact over the ten-year period, however, shocks from female labour force participation had the least impacts on CO2 emission. Environmental reforms encouraging less polluting energy and technology use is important for CO2 emission reduction, which further increases life expectancy and ultimately labour force participation rates.